Code-mixing by a content creator Gita Savitri Devi: How and why? (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2022)
Code-mixing, which is the use of two or more languages that are mixed in one utterance, is commonly practiced by bilingual or multilingual people. Then, this study aims to find out the types and the reasons for code-mixing performed by Gita Savitri Devi, a content creator, in one of her videos on YouTube channel entitled